211k views
5 votes
Cosec X - sin x= cos x cotx


User Percy Vega
by
5.3k points

1 Answer

3 votes

Answer:

See Explanation

Step-by-step explanation:


cosec \: x - sin \: x = cos \: x \: cot \: x \\ \\ L.H.S\\= cosec \: x - sin \: x \\ = (1)/(sin \: x) - sin \: x \\ \\ = \frac{1 - { \sin}^(2)x }{sin \: x} \\ \\ = \frac{ { \cos}^(2)x }{sin \: x} ...( \because \: 1 - { \sin}^(2) \theta = { \cos}^(2) \theta)\\ \\ = (cos \: x * cos \: x)/( \sin \: x) \\ \\ = \cos \: x * (\cos \: x)/( \sin \: x) \\ \\ = \cos x \: \cot x \\ = R.H.S\\ Thus \: proved \\

User RickAndMSFT
by
4.8k points